Telling in Silence - MacLaren, Stephanie (UnderCurrents: Journal of Critical Environmental Studies, 1999)
I want to tell you my story. Pass breath through my lips d weave a sorted spell. Spelling out the space between us. Breath from the bones of memo bearing witness to my soul. [...]